Micro-hardness variation of micro-phases during spheroidisation of AISI4340 steel. Issue 1 (1st January 2021) - S R, Harisha; Sharma, Sathyashankara; Kini U, Achutha; B M, Gurumurty; Hegde, Ananda
Abstract: AISI4340 steel is the medium carbon low-alloy steel has got excellent prominence as a construction material. This steel is spheroidised on heating to the intercritical temperature range by different time intervals with the objective of increasing the number and fineness of the spheroids of cementite particles. A 9 hours, spheroidisation shows better spheroids of cementite particles. To study the effect of initial room temperature structure on spheroidisation primary heat treatments like normalising and hardening are carried out for as-bought steel. Tensile property (yield strength, ultimate tensile strength and percentage elongation), hardness (Rockwell C scale) and micro-structural features and micro-hardness of micro-phases (ferrite and cementite) are studied. A continuous reduction in the tensile strength, hardness and improvement in ductility, is observed with the increase in spheroidisation time is observed in all the spheroidisation paths. Also, increased spheroidisation time shows a lesser aspect ratio for spheroids. The micro-structure shows partial spheroidisation in all the conditions with more number of spheroids in normalised condition and finer size in hardened. Drastic reduction in strength and hardness values are observed in the hardened condition during spheroidisation.